Surface Modification Of Tungsten Carbide Cobalt By Electrical Discharge Coating With Quarry Dust Powder: An Optimisation Study - Liew, Pay Jun; Yap, Ching Yee (IOP Publishing Ltd, 2020)
In this paper, quarry dust was reused as a coating material on tungsten carbide cobalt (WC-Co) via electrical discharge coating (EDC). Before the EDC process, the quarry dust was mixed well with low smell kerosene oil and surfactant Span 85 to produce a new formulation of dielectric fluid. Response surface methodology was used to investigate the effect of EDC parameters, namely peak current (Ip, 3-5 A) and pulse on time (Ton, 100-300 μs) on the characteristics of the coating surface, including its Vickers micro-hardness, surface roughness and coating layer thickness. Results showed that an increment in Ip and Ton increased the Vickers micro-hardness and coating layer thickness yet decreased the surface finish. The optimum parameters for achieving a hard surface, thick coating layer and low surface roughness are Ip = 4 A and Ton = 341 μs. The established RSM model was in reasonable agreement with the experimental outcomes, and these findings could be useful in the cutting tools, moulds and dies industries for surface modification purposes.